Penjadwalan Produksi Optimal Air Mineral Kemasan Gelas Menggunakan Pendekatan jadwal Induk Produksi - Santosa, Sesar Husen; Indrawan, Purana; Apriliani, Fany; Siskandar, Ridwan; Nabil Bayyinah, Aulia; Septiyaningsih, Lutfi (Jurnal Sains Indonesia, 2023)
The Stock buildup problem has led to an increase in product rejects at PT Marina. This condition is caused because the company cannot identify fluctuating demand conditions and only focuses on Customer Orders. Based on this problem, an analysis was carried out regarding demand using the Multiplicative decomposition forecasting technique. The company has three seasons in the demand for glass bottled water products. Based on the demand forecasting analysis results, the demand regression model is demand (y) = 153052 + 139.88 period (x). Based on the regression results, the demand forecast results are 159,819 boxes. The results of production schedules are based on the results of demand forecasting, so the Stock condition in the company is obtained, namely 3430 - 4760 boxes/week, and this condition is the optimal condition because it is below the maximum product inventory capacity in the company.